The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1086/524190
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial Structure of an Accretion Disk

Abstract: Based on the microlensing variability of the two-image gravitational lens HE 1104Y1805 observed between 0.4 and 8 m, we have measured the size and wavelength-dependent structure of the quasar accretion disk. Modeled as a power law in temperature, T / R À , we measure a B-band (0.13 m in the rest frame) half-light radius of R 1/2; B ¼ 6:7 þ6:2 À3:2 ; 10 15 cm (68% confidence level) and a logarithmic slope of ¼ 0:61 þ0:21 À0:17 (68% confidence level) for our standard model with a logarithmic prior on the disk si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
155
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(182 citation statements)
references
References 28 publications
25
155
2
Order By: Relevance
“…These values agree with the radii obtained for the lensed quasars HE1104−1805 and Q2237+0305 on the basis of their photometric variability due to microlensing (e.g. Poindexter et al 2008;Eigenbrod et al 2008;Anguita et al 2008b).…”
Section: Microlensing Of the Continuum Sourcesupporting
confidence: 89%
“…These values agree with the radii obtained for the lensed quasars HE1104−1805 and Q2237+0305 on the basis of their photometric variability due to microlensing (e.g. Poindexter et al 2008;Eigenbrod et al 2008;Anguita et al 2008b).…”
Section: Microlensing Of the Continuum Sourcesupporting
confidence: 89%
“…The study of the disk temperature profile is more complicated because multi-wavelength observations are needed to detect chromatic microlensing (Anguita et al 2008;Bate et al 2008;Eigenbrod et al 2008;Poindexter et al 2008;Floyd et al 2009;Blackburne et al 2011Blackburne et al , 2015Mediavilla et al 2011b;Muñoz et al 2011;Motta et al 2012;Rojas et al 2014). In this case, it also becomes more important to separate the contributions from strong emission lines.…”
Section: Introductionmentioning
confidence: 99%
“…There is the series of papers where the semi-empirical method of determining of the accretion disk scale R λ has been developed (see Kochanek et al 2006;Poindexter et al 2008;Morgan et al 2007Morgan et al , 2008. The authors used microlensing variability observed for gravitationally lensed quasars to find the accretion disk size and the observed (or rest-frame) wavelength relation.…”
Section: Some Results From Accretion Disk Modelsmentioning
confidence: 99%
“…Now let us estimate the value of R λ for the model of a standard accretion disk using the observational data of NGC 4258. The spatial structure of standard accretion disk have been calculated by Poindexter et al (2008). The size scaling is determined by Eq.…”
Section: Estimates Of the Magnetic Field At The Horizon Of The Black mentioning
confidence: 99%